COSMICALLY UNIVERSAL AND SPECIFICALLY SOCIAL CATEGORIES IN THE NATIVE RELIGIOUS PHILOSOPHY OF THE PERIOD FROM THE 19TH CENTURY TO THE FIRST HALF OF THE 20TH CENTURY - Іщук, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2021)
The article deals with the correlation between the cosmic and social categories from the point of view of the native religious philosophy of the period from the 18th century to the first half of the 20th century. Interaction between elements of the system “God-man-society-cosmos” is analysed. The main principles of this interaction and also their correlation between other categories of religious philosophy are defined. The most important stages by way of illustration of the opinions of Skovoroda, Solovyov, Berdyaev, and Loskiy are considered. From the comparative positions the key principles of their doctrines, which relate to the studying problem are analysed.